Improving The Students’ Speaking Skills in Formal Contexts Using Youtube Videos - Muhyiddin Aziz; Yulius Harry Widodo; Dian Palupi; Imam Mudofir; A’thi Fauzani Wisudawati; Rizka Maulina Wulandari; Ita Permatasari; Alisya Yuke (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This classroom action research (CAR) aims to improve students’ English-speaking skills in formal communication contexts. The study focuses on second-semester students of the Business and Professional Communication Study Program at Politeknik Negeri Madiun in the 2024/2025 academic year. The main problem addressed is the students’ low ability to speak English formally and fluently. The objective is to determine whether watching YouTube videos can enhance students’ formal speaking performance. The research employed both qualitative and quantitative methods. Qualitative data were obtained from students’ performance scores before and during the implementation, while quantitative data were gathered through observations, questionnaires, and interviews to compare pre-test and post-test results. The intervention used several active viewing techniques, including active viewing, freeze framing and prediction, silent viewing, and reproduction activity. The findings indicate a consistent improvement in students’ speaking abilities across all research cycles. The average scores increased from 61.1 in the pre-test, to 63.6 in post-test Cycle I, 66.6 in Cycle II, and 70.0 in Cycle III. These results demonstrate that integrating YouTube videos with active viewing techniques effectively enhances students’ formal speaking competence. In conclusion, the use of interactive video-based learning can significantly support the development of English-speaking skills in formal contexts for vocational students.